Improving the Quality of Education by Developing the Social Competency of Teachers - Candra Wijaya; Lusinta Rehna Ginting; Juli Iswanto; Melly Nadia; Arief Aulia Rahman (AL-ISHLAH: Jurnal Pendidikan, 2023)
This paper explores how the quality of education can be enhanced by developing teachers' social competence, allowing them to address the challenges posed by the rapidly changing times. The data for this study were collected through a literature review, analyzing various concepts and theories. Numerous published sources, including research papers, journals, and records, were used as references. The study's findings emphasize teachers' crucial role in improving education quality. As they directly engage with students during the teaching and learning process, teachers are primarily responsible for imparting knowledge and skills and fostering independence, intelligence, and knowledge based on individual talents and abilities. When teachers possess social competence, they become positive role models for students. In conclusion, teachers should strive to set an excellent example for their students. Having highly competent teachers can significantly enhance the overall quality of education.